6x=.75(3x-5)

Simple and best practice solution for 6x=.75(3x-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x=.75(3x-5) equation:


Simplifying
6x = 0.75(3x + -5)

Reorder the terms:
6x = 0.75(-5 + 3x)
6x = (-5 * 0.75 + 3x * 0.75)
6x = (-3.75 + 2.25x)

Solving
6x = -3.75 + 2.25x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2.25x' to each side of the equation.
6x + -2.25x = -3.75 + 2.25x + -2.25x

Combine like terms: 6x + -2.25x = 3.75x
3.75x = -3.75 + 2.25x + -2.25x

Combine like terms: 2.25x + -2.25x = 0.00
3.75x = -3.75 + 0.00
3.75x = -3.75

Divide each side by '3.75'.
x = -1

Simplifying
x = -1

See similar equations:

| 3x-.5=6x+4 | | 25=25+x | | x^8+6x^7= | | 6a-4=-22 | | 4a-18=6 | | 8x-4(-5-2)=12a | | -5a+10=-5 | | -2a-6=12 | | 2x^2=6x+3 | | 3x^2-10x-2=0 | | 3x^3-15x^2=0 | | 6x+10=6x+7-3 | | [2x-5]=3x+9 | | N=-5+2n | | 4m-10=4m+2 | | -4y+8=4(2y-2)-2(-16+8y) | | 4m-10=4m+3 | | 3(4p-9)-2(p-9)= | | -2(m-8)-3[(2m+5)]= | | 6-(5x)=4x+3 | | 2(2x+5)=8 | | 2[3x+6]-7=11 | | 4x^4-16x^2= | | 3t^2-10t+7=0 | | 7c+5=-23 | | 6x-5x+3x-5+4x= | | 3t-10t+7=0 | | 8x-3=6x-15 | | 10x^2-9xy+2y^2=0 | | 4+2y=9+2y | | 5(-8+3p)-2[2(-4p+3)]= | | -5(2t+-3)+7t=3t-8 |

Equations solver categories